Revolutionizing Healthcare: A Review Unveiling the Transformative Power of Digital Twins - Adithya Balasubramanyam; Richa Ramesh; Rhea Sudheer; Prasad B. Honnavalli (IEEE Access, 2024)
In the dynamic landscape of healthcare, Digital Twin (DT) technology has emerged as a transformative force, holding the promise of revolutionizing patient care and industry practices. This article surveys the literature over the period 2020 to 2023 on a comprehensive exploration of DT in healthcare, elucidating its roles, benefits, and implications for smart personalized healthcare. The study addresses fundamental questions concerning the transformative potential of DT, investigating its varied roles and benefits in healthcare, its revolutionary impact on the industry, and the essential requirements for crafting a DT system tailored to the demands of smart personalized healthcare. The research further unveils the key layers necessary for implementing a DT smart healthcare system, examining potential applications that extend from diagnostics to treatment strategies. Methodologically, the paper navigates through different model discussions, providing a structured approach to understanding the implementation of DT in healthcare. Despite the transformative potential, the research delves into the limitations and challenges faced by DT technology, offering a balanced perspective on its current state. In conclusion, the paper synthesizes key findings, outlines methodologies, discusses challenges, and sets the stage for future research, presenting a holistic overview of the potential, pitfalls, and pathways for integrating DT in the healthcare industry.